Stall feeding of sheep and goats: An alternative system to traditional grazing on community lands - DEVI, INDU; SHINDE, A K; KUMAR, ARUN; SAHOO, A (The Indian Journal of Animal Sciences, 2020)
Sheep and goats in the country are mostly raised on grazing resources. But these resources are gradually shrinking over the periods both in term of areas under them and also in yield and quality. On the contrary, populations of sheep and goat are increasing rapidly to meet the demand of meat. This is resulting in overstocking and overcrowding on available grazing lands and sharp deterioration of grazing resources. The intensive system (stall feeding) as an alternative to traditional grazing and semi-intensive system, may be useful to maintain pace with growing meat demand in the changing scenario of grazing resources in the country. Studies have shown that lambs and kids on stall feeding with adequate nutrition and management attain faster growth, attain slaughter weights at an early age and produce heavier carcass weights, more dressing yield and desirable lean, fat and bone contents. Although initially intensive system seems costly due to more feed cost and more capital investment, but this is justified by higher economic returns to farmers. Therefore, it can be concluded that intensive feeding system for sheep and goats is better than extensive system and at par or better than semi-intensive system for lamb and kid fattening purpose from 3–6 months of age. This review article also discusses the possibility of economic viability of sheep and goats rearing under stall feeding.